MEDIA PEMBELAJARAN BAHASA JAWA DESAIN COMPUTER ASSESTED LEARNING (CAL) - Masturoh, Titin (Acintya, 2010)
Media Of learning covering hardware is easily found while the software media has been known since theÂ development of communication and computer technology. Computer technology has supported the creationÂ aflearning media for example application such as powerpoint presentation, VCD, MP3, web, and interactiveÂ CD. In order to make Bahasa Jawa ( Javanese language) learning not boring, it is important to try computerÂ technology as the learning media. Besides, it is also supposed to increase the studying target. The purposeof this research is to ï¬nd a model of Bahasa Jawa learning and a model structure of Bahasa Jawa learningÂ by computer media (Computer Assisted Learning/CAL). Multimedia CAL tries ta make students active inÂ wing learning technology especially the function of studying source development so that the studyingÂ obstacle mainly in connection with the studying source limit can be overcome, besides. it is supposed toÂ optimalize the student role in studying actively and independently.Key words: media, educational, old Javanese. computer.